Knowledge Management System Implementation: Enterprise Resource Planning (ERP) / Nur Elya Syakirah Mohd Zamhari - Mohd Zamhari, Nur Elya Syakirah (Universiti Teknologi MARA, Selangor, 2020)
This is the era where digital age and technological era conquer the entire world. We can see many technologies been created every single day to make work more effective. Same as organization which they keep developing new system to help their business transaction and activities. For instance, for banking sector. They have core banking system that can help them in their daily business transaction such as loan, transfer money, remittance etc. Not only that, a small enterprise company also have their own system that can manage their business transaction such as point of sales (POS) system. By doing that, people are depending on technology to make the world function more efficiently.